Glossophobia of University Students in Malaysia - Andrew, Yau-hau Tse (2012)
Glossophobia, or the fear of public speaking, is not uncommon. Students may fail at work or at school because of anxiety. The objective of this research is twofold: a) to survey if females have greater amount of anxiety when giving a public speaking presentation than males; and b) to investigate if the teaching of affective learning strategies helps reduce their public speaking anxiety. A 2x2 between subjects factorial ANOVA was calculated comparing the anxiety scores for females giving a speech in front of all female or male audience and also the male scores when speaking in front of all female or male audience. Next, McCroskey’s (1998) ‘Personal Report of Public Speaking Anxiety (PRPSA) questionnaire was used to collect data on their feelings towards giving a speech. The same questionnaire was administered at the beginning and end of a course in public speaking. Paired T-test was employed to measure the difference of nervousness in the same semester. A total of 202 university technical students majoring in engineering and computing were chosen as subjects. The findings revealed that a) the hypothesis was not supported that females would have a higher amount of anxiety than males and b) male and female students significantly experienced less anxiety after they had been taught how to manage their stress. Further research is necessary to i) scrutinize gender differences in public speaking anxiety and ii) evaluate the casual nature of public speaking among university students.